Estratégias de operacionalização de uma linha de cuidado para pessoas em uso de substâncias psicoativas no contexto da rede de atenção psicossocial - Paula, Francisca Mechi Ribeiro dos Santos de (Universidade Federal de São Carlos, 2025)
This dialogical and interpretative study aimed to collectively construct strategies for the operationalization of a care pathway for people with harmful use of psychoactive substances. The research was conducted in a health region of the state of São Paulo, composed of six small municipalities (up to 70,000 inhabitants). It was developed in three stages: (i) data collection from the National Registry of Health Establishments and the Demographic Census to map the Psychosocial Care Network (RAPS) facilities and population by municipality; (ii) exploratory interviews with the Regional Health Department and local managers, carried out through an electronic form in five municipalities; (iii) six workshops with 17 professionals from the Unified Health System (SUS), including representatives from the Regional Health Department and participating municipalities, using elements of strategic health planning with a dialogical and reflective approach, in hybrid format (in-person and remote). Data were recorded manually, through audio recordings and photographic records, forming unique field diaries. The analysis of the first stage enabled the description and mapping of the local care network, while the analysis of interviews and workshops focused on two main axes: the group process developed in the workshops and the final product, represented by the agreed proposal of operational strategies for the care pathway targeting people with harmful use of psychoactive substances. The proposed care pathway considered the Psychosocial Care Model, the Harm Reduction approach, and especially the specificities of the municipalities, in which primary care (with multiprofessional teams) predominates, and 4 out of 6 municipalities only have CAPS I services. These factors posed challenges to structuring a singularized care pathway. The results highlighted the articulation between technical-scientific knowledge and collective production as a strategy to strengthen the intermunicipal network, in addition to incorporating best evidence in mental health related to management, training, and care in this context. Scenarios of institutional and structural violence reproduction were also identified, as well as weaknesses in psychosocial and interprofessional care, alongside the predominance of practices centered on medicalization and institutionalization through hospitalization—factors that reinforce user marginalization and vulnerability. As the final product of the workshops, a singularized proposal for the operationalization of the psychoactive substances care pathway was agreed upon, collectively constructed and oriented to the regional reality of small municipalities, culminating in the elaboration of two technical manuals with guidelines for its implementation. It can be concluded that the critical success factors lie in the collective and dialogical strategy for planning a singularized care pathway, in articulating care management with continuing education, in ensuring the technical-scientific validity of practices, and in assuming an emancipatory ethical-political guideline.
Strategies for implementing a care pathway for people who use psychoactive substances within the context of the psychosocial care network
Keywords: Saúde mental; Psicotrópicos; Serviços de saúde; Reforma psiquiátrica; Redução de danos; Mental health; psychotropic substances; health services; psychiatric reform; harm reduction; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA; 3. Saúde e Bem-Estar